Creating an enabling environment for affordable housing in Saudi Arabia: a critical review of the Kingdom’s vision 2030 - Alhamoudi, Abdullah Mazen; K'Akumu, Owiti A. (Frontiers in Built Environment, 2026)
PurposeSaudi Vision 2030 marks an attempt to create an enabling environment for economic development in the Kingdom of Saudi Arabia. This article constitutes an evaluation of its endeavour to create an enabling environment for the production and consumption of affordable housing. The need to do this has arisen from the government’s intention to transform itself from being a provider to an enabler of housing which involves the introduction of housing as a commodity to be bought and sold in the market.MethodologyThe main method of this paper was based on reviewing and evaluating the resultant enabling environment in terms of six analytical factors involving opportunities and constraints created in the input, output and regulatory environments.FindingsThe main finding is that the resultant environment has prioritized demand factors over supply factors over the provision of affordable housing. This has led to the recommendation that the enabling environment should be tweaked to factor in items in the input environment that would lead to lower costs and more affordable housing.OriginalityThis research focused on a less discussed subsystem of housing in housing research, an evaluation of the endeavour to create an enabling environment for the production and consumption of affordable housing.